Training and labor performance law in the Regional Agricultural Directorate. Case: Amazonas - Figueroa Sánchez, Armando Edgardo (2020)
The objective was to determine how the training activities are related to the performance of the servers of the offices of the Ministry of Agriculture of Amazonas, in the year 2019. It was a descriptive-relational investigation. A sample of 73 workers and 16 direct chiefs of the servers were established. It was found that, regarding the planning of the training and performance of the workers, an association was found, among these variables, finding a correlation of 0.50. There is also an association with the execution of training and the average performance, finding a correlation of 0.58. All this indicates that, although workers do not receive good training, their job performance is also regular. 62% of the workers expressed their agreement that the training contributes to the performance of the servers, presenting a similarity with (Mayurí, 2008), who found that 60% of the workers indicated that the training could always increase The performance of the workers